2002
DOI: 10.1081/ada-120015872
|View full text |Cite
|
Sign up to set email alerts
|

Arrestees' Perceived Needs for Substance-Specific Treatment: Exploring Urban–Rural Differences

Abstract: An interview study among a group of arrestees in seven county jails was conducted in the state of Ohio between June 1999 and September 2001, examining the prevalence of alcohol and drug dependence within the group and assessing the need for substance-abuse treatment. Four of the county jails where interviews were conducted are in urban areas, and three are in rural areas. The present study focused on demographic variables, situation-related factors, current drug dependence diagnoses, past treatment experience,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2004
2004
2023
2023

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 50 publications
0
8
0
Order By: Relevance
“…must also be asked whether the locales in which arrestees reside (i.e., urban versus rural) may factor into any gender differences. Working with the same data set employed in the present study, Lo and Stephens (2002) found no significant relationships between residential location and current dependence on specific drugs among arrestees. Their study, however, did show that locale could moderate the impact of some background variables on arrestees' perceived needs for substance-specific treatment.…”
Section: Discussionmentioning
confidence: 47%
See 1 more Smart Citation
“…must also be asked whether the locales in which arrestees reside (i.e., urban versus rural) may factor into any gender differences. Working with the same data set employed in the present study, Lo and Stephens (2002) found no significant relationships between residential location and current dependence on specific drugs among arrestees. Their study, however, did show that locale could moderate the impact of some background variables on arrestees' perceived needs for substance-specific treatment.…”
Section: Discussionmentioning
confidence: 47%
“…The design of the present study, along with most measures used in it, were described in detail elsewhere (Lo & Stephens, 2002). Its target population was persons arrested in the state of Ohio between June 1, 1999 andSeptember 30, 2001.…”
Section: Methodsmentioning
confidence: 99%
“…The Arrestee Drug Abuse Monitoring interview schedule and the Diagnostic Interview Schedule were used to construct the questionnaire used in the present study. Readers may see Lo and Stephens (2002) for details of the research project's design and sample.…”
Section: Methods Designmentioning
confidence: 99%
“…This was the case for older arrestees, from rural counties in the USA (from 81,000 to 110,000). They reportedly lacked motivation for opiate specific treatment because of their identity as drug users and unwillingness to challenge this understanding of self by presenting at a treatment service (Lo & Stephens, 2002). Warner and Leukefeld (2001) noted that some rural residents do not want treatment as their AOD use is not regarded as a problem.…”
Section: Variations In Drug Use and Treatment Experience By Ruralitymentioning
confidence: 99%